Dimensões do desafio nos videojogos - João Miguel da Costa Magalhães (2022)
This dissertation proposes a qualitative classification of the various types of challenge that can be found in videogames by means of a framework, with the objective of assisting in game design and in game development. The framework departs from four basic types of challenges present in the videogames were identified from (Vahlo and Karhulahti 2020): Physical, Cognitive, Emotional and Social. The classification of these four types allowed us to develop new types of hybrid challenges based on the combination of different challenges: Physical-Cognitive, Physical-Emotional, Physical-Social, Socio-Cognitive, Socio-Emotional, Emotional-Cognitive. Our framework allows us to instrumentalize these concepts in a deck of cards format. This dissertation proposes that the qualitative challenge analysis be constantly studied for game design and development. It is intended that the results achieved can contribute to the conception and design of this category of video games.